SOSIOLOGI PENDIDIKAN DI ERA KECERDASAN BUATAN: ANTARA INOVASI PEMBELAJARAN DAN KETIMPANGAN DIGITAL DI TINGKAT SEKOLAH DASAR - Wahyu Haspri; Haryanto, Sigit; Hindarto, Hindarto; Jasno, Jasno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores educational sociology in the AI era, focusing on the intersection of learning innovation and digital inequality in elementary education. While rapid advancements in artificial intelligence offer new avenues for adaptive, interactive, and personalized learning, their implementation across elementary schools remains highly uneven. This disparity is driven by gaps in internet access, device availability, teacher competence, student digital literacy, and socioeconomic backgrounds. Utilizing a qualitative descriptive design through library research, this study gathered data from scientific articles, books, policy documents, and institutional reports, which were then evaluated using content analysis. The findings reveal that although AI effectively assists teachers in curriculum design, assessment, and student engagement, digital inequality hinders the fair distribution of these benefits. Viewed through the lens of educational sociology, this gap reflects the reproduction of social inequality via unequal access to resources—where well-funded schools successfully adopt AI while under-resourced ones lag. Consequently, integrating AI in elementary schools requires systematic support through infrastructure equity, teacher training, student literacy programs, and inclusive policies.